Termodinâmica de líquidos iônicos via simulação computacional - Prado, Carlos Eduardo Resende (2006)
In this work classical molecular dynamics was used to study the pure ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate, [BMIM]+[BF4]-, and some solutions based in it. The OPLS-AA force field and CHelpG derived charges were used to represent the interactions. The results obtained for the pure liquid agreed well with theoretical and experimental data available. The diffusion of ions in this liquid was investigated through the solvation of KCl salt. The result showed that the diffusion of K+ and Cl- are small when compared with the diffusion observed in aqueous solution. The results obtained for K+ and Cl- ions are also small compared to the diffusion regime observed for the ionic pair [BMIM]+[BF4]- in water. The solvation of an oligopeptídeo, formed by six alanines, aminoacids in this liquid was investigated at two temperatures, 300K and 400K. The effect of water molecules in the oligopeptide neighborhood was also investigated. The spc-model (Simple Point Charge) was used to represent the water molecules. Compared to the peptide behavior in water the results obtained in the ionic liquid showed that the peptide structure was constrained. It was also observed that the presence of water molecules near the oligopeptide increased its conformational mobility. The effect media polarization on the electronic structure of ionic liquid components was analyzed investigating the dipole momentum distribution for 1,4-dimethylimidazolio cation in both isolated and in condensed phase. The dipole distribution for chloride in condensed phase was also performed.